High Temperature Ceramic Matrix Composites 8: Ceramic Transactions, Volume 248 - Zhang, Litong; Jiang, Dongliang (Ceramic Transactions Series, 2014)
This proceedings contains 78 papers from the 8th International Conference on High Temperature Ceramic Matrix Composites, held September 22-26, 2013 in Xi'an, Shaanxi, China. Chapters include: Ceramic Genome, Computational Modeling, and Design Advanced Ceramic Fibers, Interfaces, and Interphases Nanocomposite Materials and Systems Polymer Derived Ceramics and Composites Fiber Reinforced Ceramic MatrixComposites Carbon-Carbon Composites: Materials, Systems, and Applications Ultra High Temperature Ceramics and MAX Phase Materials Thermal and Environmental Barrier Coatings